-تشابُك الأنساق الثقافية في رواية -القاهرة الصغيرة - عوادي,يسمينة (University of Eloued جامعة الوادي, 2025)
تبحث هذه الدراسة في الأنا العربية والغيرية الـمُتَخَيَّلتين في النص السردي الروائي، من خلال شخصيات متعددة المشارب والجندر في رواية "القاهرة الصغيرة ،حيث تتشابك الأنساق والمصالح ، لتطرح الرواية أسئلة حرجة حول المأزق الهوياتي للأنثى والذكر ومرجعيات التمييز الجندري، وكذا سطوة الأبوية في الثقافة العربية،التي تعتبر صنما بحسب الرواية،كما عالج هذا البحث إشكالية الإسلاموفوبيا التي تصنعها بعض الفرق الدينية المتطرفة ويعممها الآخر(الغرب) في فهم صورة كل المسلمين .عرضت الدراسة نظرة الآخر لصورة الإسلام في قالب كوميدي إيطالي ساخر؛جعل الرواية تأخذ أبعادا مختلفة ؛لتُعرّي السردية الغربية حول نظرتهم للعرب والإسلام.Abstract: This study examines the imagined Arab self and otherness in the narrative text, through characters of various backgrounds and genders in the novel " Alqahira saghira," where systems and interests intertwine, raising critical questions about the identity crisis of both female and male, and the references of gender discrimination, as well as the dominance of patriarchy in Arab culture, which is considered an idol according to the novel. This research also addressed the issue of Islamophobia, which is created by some extremist religious groups and generalized by the other (the West) in understanding the image of all Muslims. The study presented the other's view of the image of Islam in a satirical Italian comedic framework; this made the novel take on different dimensions, exposing the Western narrative regarding their perception of Arabs and Islam
للروائي: عمارة لخوص
Keywords: الجندر; الأنساق; عمارة لخوص; Gender; Systems; Patriarchy; Islamophobia; Western